1994
DOI: 10.1111/j.1445-2197.1994.tb04562.x
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine Preserves Non‐specific Immune Function After Colonic Resection for Cancer

Abstract: Fifty consecutive patients undergoing resection of colorectal cancer were randomized to either receive cimetidine at a dose of 400mgbd for a minimum of 5 pre-operative days, then intravenously for 2 postoperative days, or to act as controls.Baseline immune function was determined in all patients by in vitro testing of lymphocyte proliferation (LP) in response to mitogen. skin testing for cell mediated immunity (CMI) and measurement of lymphocyte subsets. Immune function was retested in both groups on the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…However, the exact mechanism by which cimetidine may exert an anticancer effect remains uncertain. cimetidine is thought to exert its effect by blocking high peritumoral concentrations of histamine and increasing systemic immunoreactivity via H 2 receptor antagonism of circulating T suppressor cells or maintenance of natural killer cell activity (19)(20)(21). However, Rajendra et al (22) have demonstrated that cimetidine has a direct antiproliferative effect in the absence of histamine type 2 receptors and the induction of apoptosis.…”
Section: Cimetidine Inhibits the Growth Of Transplantable Tumorsmentioning
confidence: 99%
“…However, the exact mechanism by which cimetidine may exert an anticancer effect remains uncertain. cimetidine is thought to exert its effect by blocking high peritumoral concentrations of histamine and increasing systemic immunoreactivity via H 2 receptor antagonism of circulating T suppressor cells or maintenance of natural killer cell activity (19)(20)(21). However, Rajendra et al (22) have demonstrated that cimetidine has a direct antiproliferative effect in the absence of histamine type 2 receptors and the induction of apoptosis.…”
Section: Cimetidine Inhibits the Growth Of Transplantable Tumorsmentioning
confidence: 99%
“…Administration of CIM has been found to preserve, to some degree, the patients' perioperative immunity [5,6] , to improve the survival of patients with colorectal cancer, melanoma, and renal cell cancer [7][8][9][10][11][12][13][14][15] . Although it is not clear whether this effect of CIM on cancer is direct or indirect, it has been proposed that CIM may act by enhancing the host immune response to tumor cells [16,17] or by blocking the cell growth-promoting activity of histamine in cancer cell lines [14,[16][17][18][19][20] . In this study, we used CIM in the perioperative period as an adjuvant immunomodulatory agent, and studied its effects on peripheral blood lymphocytes, NK cells and TIL in a randomized controlled clinical trial in patients with GI cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Experimentally, CIM has been shown to enhance a variety of immunologic functions both in vivo and in vitro, including decrease in the relative abundance or function of Treg cells in several studies. [12][13][14] Indeed, Wang J et al 14 reported that the use of CIM as a vaccine adjuvant in mice could induce expression of pro-inflammatory cytokines such as IL-6 and IL-12 and down-regulate expression of anti-inflammatory cytokines, including IL-10 and TGF-b. The immune adjuvant effects of CIM have been confirmed by several other groups.…”
Section: Introductionmentioning
confidence: 99%